Uslub Al-Tasybih: Kajian Struktur dan Fungsinya dalam Penafsiran Al-Qur’an - Azhar Syauqy RM Saeed; Andi Miswar; Mohamad Harjum (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article examines in depth the structure and function of uslub al-tasybih in Qur'anic interpretation using the approach of 'ilm al-balagah. Tasybih, as one form of uslub al-bayan, plays an important role in clarifying meaning, embellishing expression, and strengthening the divine message within the text of the Qur'an. This study analyzes the pillars of tasybih (musyabbah, musyabbah bih, adat al-tasybih, and wajh al-syibh) and elaborates its rhetorical functions, which are classified into six forms: bayan imkan al-musyabbah, bayan hal al-musyabbah, bayan miqdar hal al-musyabbah, taqrir hal al-musyabbah, tazyin al-musyabbah, and taqbih al-musyabbah. The study employs a library research method, drawing on classical and contemporary works of Qur'anic exegesis.